Complex Training Methods and Maximal Strength: an Experimental Study on Judo Athletes - Geraldi Novian; Komarudin, Komarudin; Dikdik Zafar Sidik; Ira Purnamasari; Fitri Rosdiana (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2024)
Maximal strength is one of the important components for judo athletes. Maximal strength helps athletes perform throwing techniques well when competing. Therefore, the right method is needed to increase the athlete's maximal strength. This study aims to examine the effect of complex training methods on the maximal strength of judo athletes, where complex training methods have been shown to provide positive benefits for various components of athletes' physical conditions. An experimental method using a one-group pretest-posttest design was used in this study. The treatment in the form of a training program using the complex training method for eight weeks was given to 20 Indonesian judo athletes. Maximal strength tests using squats and bench press were carried out before and after treatment. Data analysis was carried out using the t-test. This study provides results that show that the complex training method has been proven to be able to significantly increase the maximal strength of judo athletes. In addition, the results also show that there is a difference in the percentage of increase between male and female athletes. This study concludes that the complex training method can be used as one method to increase the maximal strength of judo athletes.